Interpretación de factores de infección del lugar de inserción del catéter venoso central en la unidad de cuidados intensivos padiátrica - Palomo Colcha, Ximena Elizabeth (2025)
The work of the nursing professional in the Intensive Care Unit is born from the need to specialize the care that is directed to critical patients with different pathologies of all ages, the first intensive care units in Ecuador were created between the 1970s in Ecuador. The present study aimed to carry out a systematic review of several scientific articles from our country and also from other countries, in the first instance the epidemiological description of the Under Secretariat of Public Health Surveillance of Ecuador was carried out where the complications of greater prevalence during hospitalization in an Intensive Care Unit of adult and pediatric patients have been determined. The characteristics of the Intensive Care area of both adults and pediatrics, patients with different pathologies who are hospitalized in this area, were also described. The Central Venous Catheter was defined, its characteristics, utilities, the different types of insertion, as well as its advantages and disadvantages. The factors of infection of the site of insertion of the Central Venous Catheter as a subject of study was widely addressed, thus the infections associated with the Central Venous Catheter were determined, the complications during its use, nursing care in the prevention of these infection factors, activities for the maintenance of the Central Venous Catheter, educational actions for health personnel and recommendations of the nursing professional to timely identify the infection factors of the catheter insertion site and thus prevent them